HUMANITY PEDAGOGY AND TECHNOLOGY OF HOLISTIC APPROACH - Feruza Aminovna Turakulova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the content and purpose of humanitarian pedagogy and technology of holistic approach stated.